1978
DOI: 10.1159/000315982
|View full text |Cite
|
Sign up to set email alerts
|

Fractured Somatotopy in Granule Cell Tactile Areas of Rat Cerebellar Hemispheres Revealed by Micromapping; pp. 106–115

Abstract: We defined spatial patterns of tactile projections to cerebellar cortex of anesthetized albino rats using microelectrode micromapping methods. Low threshold natural stimulation of cutaneous mechanoreceptors of specific body structures evokes brisk, short latency, localized responses within the granule cell layer. These projections terminate within columnar assemblies of granule cells within the folia of crus I, crus II and paramedian lobule of the cerebellar hemispheres. These columnar inputs appear as individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
84
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 0 publications
9
84
2
Order By: Relevance
“…Although the precise somatotopy of climbing fibre projections to crus 1 is not known, it has been shown that the mossy fibre projections to crus 1 convey somatosensory input mainly from the mystacial vibrissae and the surrounding skin, while the somatosensory input from the lips predominantly targets crus 2 (Shambes et al . ). The stimuli were given using a Von Frey filament (target force = 0.686 mN) attached to a piezo actuator.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the precise somatotopy of climbing fibre projections to crus 1 is not known, it has been shown that the mossy fibre projections to crus 1 convey somatosensory input mainly from the mystacial vibrissae and the surrounding skin, while the somatosensory input from the lips predominantly targets crus 2 (Shambes et al . ). The stimuli were given using a Von Frey filament (target force = 0.686 mN) attached to a piezo actuator.…”
Section: Resultsmentioning
confidence: 97%
“…The predominant somatosensory input to crus 1 stems, according to the classification of mossy fibre inputs, from the facial whiskers (Shambes et al . ). Here, we show at single cell resolution that climbing fibres indeed do convey somatosensory input from different facial areas, with Purkinje cells having the same receptive fields being located preferably in each other's proximity.…”
Section: Discussionmentioning
confidence: 97%
“…Short‐latency excitations of mossy fibres and Purkinje cells in Crus I and II have been reported to be evoked principally by trigeminal inputs (e.g. Shambes et al 1978; Bower & Woolston, 1983), like the excitations of Golgi cells (Vos et al 1999; and Fig. 5).…”
Section: Discussionmentioning
confidence: 97%
“…Analyses of information processing within the cerebellar cortex have largely focused on the precise spatial organization of mossy fibre inputs. In the rat, the best‐studied region of cerebellar cortex in terms of input is Crus II in the posterior lobe, and in this region the granule cell layer comprises ‘patches’ with focally specific mossy fibre inputs (Shambes et al 1978). Most of the patches in Crus II have both direct inputs from specific territories of the trigeminal nerve, and long loop cerebropontocerebellar inputs via the sensorimotor cortex conveying information from the same receptive field, which are reflected in the responses of granule cells and Purkinje cells (Bower & Woolston, 1983; Bower & Kassel, 1990; Morissette & Bower, 1996) and also Golgi cells (Vos et al 1999; Holtzman et al 2006).…”
mentioning
confidence: 99%